(untitled) (University Arena, 2025)
Background. The development and spreading of physical activities are processes that contain different fields of activity, therefore we need a model of the psychomotor demands, specifically for the specializations and conditions of every student’s life. We are talking about a decision drawn by analyzing interdisciplinary data with different content, in order to obtain positive results during P.E classes such as: the optimization in the process developing the body aesthetic and the raise of self-esteem Objectives: The study took place between the years 2016-2017 and included only female student prospects and with the means of the data we gathered and analysed, we set off to demonstrate the efficiency of the applied programmes, considering the level of effort in certain moments of the day or week, along with the preferences for certain subjects which undoubtedly enhanced the aesthetic evolution of the female body. Methods: We applied a closed, social Market Research quiz, adapted from „The Cooper Institute for Aerobics Research” (1999) and applied to a number of 120 female students from first and second year. The structure of the quiz was made of 6 basic categories and subcategories of physical activities, each containing 5 questions reffering to: the daily schedule, (7,00 şi 14,00) the activity type, rest, work level intensity (low, medium, high) monitoring the activities during the whole week. Results. Quantitative analysis highlighted the following: 52.5% of the female students believe they have problems regarding their physical condition, 63% of them are not pleased with their appearance. Qualitative analysis showed the following: 97% of female students are aged between 18 and 21 and 79% live in an urban environment, 21% took a mild part in physical activity in their last year of highschool, 4% were excluded on medical reasons. Conclusions. After applying the quiz and debating on the results, we could conclude the following: that physical activities take place mostly on Mondays and Fridays; activities for improving physical condition take place mostly on Mondays, Wednesdays and Fridays; competitive or recreative physical activities take place mostly on Tuesdays and Fridays; phyisical activities for muscle tonification take place mostly on Mondays and Fridays; physical activities for improving mobility and life quality take place mostly on Tuesdays and Thursdays; other activites than phyisical activities take place mostly on Tuesdays and Wednesdays.